Tantangan Dalam Mengimplementasikan Kurikulum Merdeka Pada Pembelajaran Pendidikan Agama Islam: Studi Kasus SMP El Dzikir Islamic Boarding School - Hakim, Harend Abdul; Mustofa, Triono Ali (Jayapangus Press, 2025)
This study aims to analyze the implementation of Merdeka Curriculum in learning Islamic Religious Education (PAI) at El Dzikir Islamic Boarding School. Using a descriptive qualitative approach with a case study method, the research explores the learning practices, challenges, and positive impacts of implementing this curriculum in a pesantren environment. Data were collected through in-depth interviews with the principal and PAI teachers, non-participatory observation, and analysis of learning documents. The results showed that the implementation of Merdeka Curriculum has been running quite well although it has not been maximized. The implementation stages include planning (including teacher training and socialization to student guardians), implementation (with an active learning approach and project-based), and evaluation both test and non-test based. Learning facilities such as projectors and Chromebooks are supporting factors, while the Pancasila Student Profile Strengthening Project (P5) has successfully integrated Islamic values through activities such as Quranic Camp. Key challenges include teachers' and learners' adaptation to the new curriculum and learners' difficulty maintaining focus during digital learning and outside the classroom. Positive impacts include more dynamic learning, development of learners' independence and critical thinking skills, and a more flexible and creative role for teachers. This research shows that pesantren-based educational institutions are able to adapt Merdeka Curriculum while maintaining Islamic values in the learning process. The findings contribute to the development of a national curriculum implementation model in the context of Islamic education and provide practical recommendations for optimizing the integration of religious values with contemporary pedagogical approaches according to the Pancasila Learner Profile.